The Paradox of the International Law Development: A Lesson from Covid-19 Pandemic Management - Ria Wierma Putri; Yunita Maya Putri; Febryani Sabatira; Orima Melati Davey; Himal C Arya (Lex Scientia Law Review, 2023)
The COVID-19 pandemic has had a global impact since 2019. As countries gradually recover, there are lessons to be learned for the development of international law. The World Health Organization (WHO) plays a crucial role in maintaining global health order. Governments have implemented measures like quarantine, travel restrictions, and vaccination programs, but challenges remain due to varying capacities and ideological differences. Some states prioritize national interests over global mandates from the WHO. This turns the pandemic issue into an evolution of the global legal order. This article offers a unique examination of the WHO's role in managing the COVID-19 pandemic. It aims to provide lessons and analytical approaches for reforming and strengthening health institutions while fostering global unity in the face of unprecedented challenges. The research also presents how the pandemic has impacted the development of the international law by addressing current perspectives, challenges, and potential strategies